The effect of poly(butylene adipate-co-terephthalate) (PBAT)/ oil palm frond (OPF) composite with palm stearin as compatibiliser / Istikamah Subuki ... [et al.] - Subuki, Istikamah; Azrin, Muhammad Danish Zuhairi; Mohamed Ali, Ameer Azali; Hanipah, Suhaiza Hanim; Ramlee, Nur Azrini (UiTM Press, 2025)
The chemical composition of palm stearin (PS), with its highly saturated fats and triglycerides, makes it a potential candidate to serve as a compatibilizer. This study investigated the effect of PS as a compatibiliser on the thermal and mechanical properties of poly(butylene adipate-co-terephthalate) (PBAT)/oil palm frond (OPF) composites. In this paper, a biodegradable composite was prepared by blending the PBAT with OPF as a filler, where it was subsequently mixed with PS as a compatibiliser. A mixture of PBAT, OPF, and PS was melted using an internal mixer at 160 ℃ and 60 rpm for 12 minutes. The various formulations were then subjected to torque evaluation and thermal and mechanical analysis to characterise the samples. The torque analysis indicated that the PBAT was compatible with 30 wt.% OPF. The chemical bond between PS, PBAT, and OPF is responsible for the decrease in the melting point and degradation temperature of the PBAT/OPF composite with increasing PS concentration. The presence of PS in the PBAT-OPF composite improved its flowability and moulding process. Accordingly, the tensile strength and ductility showed improvement with the addition of 7.5% PS in the PBAT70/OPF30 composite. Meanwhile, the addition of PS resulted in a decrease in Young's modulus. The results indicated the suitability of the PS as a compatibiliser for the PBAT/OPF composite.